PERKEMBANGAN KADASTER KELAUTAN DI INDONESIA - Eka Djunarsjah; Bob Gamaliel Marbun (Universitas Pendidikan Indonesia (UPI), 2022)
In the management of marine resources, a marine cadastral system is needed in the administration of water space objects. This study aims to examine the development of Indonesian marine cadastre in terms of four the main aspects of marine cadastre, namely legal aspects, institutional aspects, technical aspects, and human resources aspects, as well as comparing the status of Indonesian marine cadastre with the marine cadastre status of other countries.. The results of this study indicate that from the legal aspect, Indonesia does not yet have a law that specifically becomes the legal basis for the application of marine cadastre in Indonesia. From the institutional aspect, it can be seen that the implementation of marine cadastre in Indonesia is still managed sectorally by ministries/agencies related to water space. Indonesia has developed technical implementation of marine cadastre in Indonesia.Keywords: Human Resources Aspects, Legal, institutional, Marine cadastre, Technical,